Conformal sublobar electroresection with volume optimization achieves greater parenchymal preservation than stapler in wedge resection: a volumetric analysis - Zhang, Xining; Liu, JingWei; Zhang, ShiJie; Li, Jian (Frontiers in Oncology, 2025)
BackgroundWedge resection is widely applied for small pulmonary nodules, yet stapler-based approaches may result in unnecessary parenchymal sacrifice. The CONSERVO (Conformal Sublobar ElectroResection with Volume Optimization) technique is an electrosurgical, shape-respecting method designed to maximize parenchymal preservation while maintaining oncologic and procedural safety.MethodWe retrospectively included 104 patients who underwent stapler-based or CONSERVO wedge resection for solitary pulmonary nodules at our center between 2023 and 2024. Propensity score matching and multivariable linear regression were conducted. Key outcomes included lobe to lung volume ratio loss, operative time, incision length, intraoperative bleeding, drainage volume, and complication rate.ResultBaseline characteristics were well-balanced between groups. The CONSERVO group demonstrated superior parenchymal preservation, with significantly lower lobe-to-lung volume ratio loss (4.66% [IQR 1.68%-7.02%] vs. 11.17% [IQR 8.91%-14.48%], p<0.001) and lobe volume loss (149855.5 ± 221949.3mm3 vs. 220374.6 ± 189597.7mm3, p<0.001). Multivariable regression analysis confirmed the parenchyma saving effect of the CONSERVO technique (Coef. = -0.133, 95% CI: -0.182 to -0.084, p < 0.001). Additionally, the CONSERVO group was associated with a shorter incision length (23mm [IQR 20-25mm] vs. 35mm [IQR 30-40mm], p<0.001). The operative time was longer in the CONSERVO group (133min [IQR 103-170min] vs. 62min [IQR51-104min], p<0.001). No significant differences were observed in thoracic drainage duration, postoperative drainage volume, or pathological outcomes.ConclusionThe CONSERVO approach achieves meaningful parenchymal preservation and offers additional advantages such as smaller incision size while maintaining oncologic and procedural safety. It may be particularly suited for patients with limited pulmonary reserve or those requiring multiple resections, as well as nodules located close to hilar structures.